The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1677/joe.0.1580153
|View full text |Cite
|
Sign up to set email alerts
|

The role of the tissue renin-angiotensin system in the response of the rat adrenal to exogenous angiotensin II

Abstract: The tissue renin-angiotensin systems (RAS) may have specific roles that complement those of the systemic RAS. In the adrenal, the tissue RAS has been implicated in the regulation of glomerulosa tissue growth and function, and in mediating the response of the tissue to stimulation by ACTH and potassium ions.To examine the role of the rat adrenal tissue RAS in its response to angiotensin II stimulation, adrenals were incubated either as bisected glands or as separated capsular glands (largely glomerulosa) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies using bisected whole adrenal gland showed that Cap inhibited the response of aldosterone to exogenous Ang II stimulation by preventing the conversion of aldosterone from its precursor. These data suggested that the adrenal could regulate Ang IIstimulated aldosterone synthesis and release through the local RAS, independently of the circulating RAS (47). Other studies further demonstrated the dissociation between the circulating RAS and the adrenal-specific RAS in regulating aldosterone production.…”
Section: Fig 7 Effect Of E 2 On Adrenal At 1 R Expression After Higmentioning
confidence: 83%
“…Studies using bisected whole adrenal gland showed that Cap inhibited the response of aldosterone to exogenous Ang II stimulation by preventing the conversion of aldosterone from its precursor. These data suggested that the adrenal could regulate Ang IIstimulated aldosterone synthesis and release through the local RAS, independently of the circulating RAS (47). Other studies further demonstrated the dissociation between the circulating RAS and the adrenal-specific RAS in regulating aldosterone production.…”
Section: Fig 7 Effect Of E 2 On Adrenal At 1 R Expression After Higmentioning
confidence: 83%
“…Many lines of in vitro evidence (obtained by the use of capsular zona glomerulosa strips, adrenal slices, or zona glomerulosa cell cultures) suggest that adrenal RAS controls aldosterone secretion. ACE inhibitors were found to lower either basal (20) or K ϩ -and ACTH-stimulated aldosterone output by rat zona glomerulosa (2,14,17,18,21) and basal aldosterone yield by cultured bovine (9) and human adrenal tissue (5), as well as by K ϩ -stimulated aldosterone release by human adrenocortical NCI-H295 cell line (8). A selective AT 1 receptor antagonist was reported to block both basal and agonist-stimulated aldosterone secretion from cultured bovine zona glomerulosa cells (7) and K ϩenhanced aldosterone production from the NCI-H295 cell line (8).…”
Section: Discussionmentioning
confidence: 98%
“…This local production of the bioactive peptides is not necessarily dependent on the local expression of all components of the local tissue RAS, since it is also possible to take up components from the circulation, such as renin. Furthermore, besides presence of Angiotensin II and Angiotensin (1–7), expression of AT1R, AT2R, and Mas-receptor human reproductive tissue is needed in order to mediate the local impact of the RAS for physiological and pathological processes, including follicle maturation, fine-tuning of the regulation of reproduction, angiogenesis as well as tumor cell proliferation (1518). An influencing effect on cancer has been described for different tumor types already during the last two decades (19, 20).…”
Section: Introductionmentioning
confidence: 99%